RANCANG BANGUN ALAT PENGERING TIPE RAK DENGAN SYSTEM HYBRID UNTUK USAHA PISANG SALE - Muhammad Makky; Vonny Indah Mutiara; Azrifirwan Azrifirwan (Jurnal Teknologi Pertanian Andalas, 2008)
The Application of solar drying for food commodity has been widely used in Indonesia. This Cost efficiently drying technique become a commonly use since it is easy to build, cheap and could be applied in any area as long as it has enough sun intensity trough out the year. Since this type of drying very dependent to sun, it has a limitation to be used in places where rainy days are longer than sunny days. This research has been conducted to solve the problem by implementing a rack type solar dryer with another heat resource which is a gas stove.A rack type solar dryer has build with a secondary heat source using gas fireplace. The rack build from light material using fickle timber and aluminums made it become portable. The dryer build with a knock down system, so it can be assemble and disassemble to reposition it in area with better solar recipient. Total weight of this dryer is only 32 kg and consists of four major parts. The first part is solar collector, height 22 cm, width 85 cm and length 187 cm at an angle of 5o to the horizontal axle. The solar collector constructed in wave shape to maximize the acceptance area of solar ray. The collector builds in a glass house frame to optimize the heat dissipation so it can reach Working temperature of 65oC. The fireplace was the second part, and made from rust proof steel. It has dimension of 85 cm width, 65 cm length and 22 cm height. The fireplace filled with 6 liters sand to maximize heat collect from the stove. The stove was the third part; consist of a gas stove and a 5 kg gas tube. The stove can be turn on in rainy day or at night as an alternative heat source for drying process. The tube contain of 3 kg gas that can fuel the stove for 60 hours. The last part was the drying rack with 360 liters volume. It has five cabinets and can fill up to 1500 pieces of dried banana. The rack equipped with a shell type door to simplify the containing process.